A review of chemical demineralization and desulphurization of high ash & high sulphur lignite coal - Ahmed Lakhmir, Mansoor; Ahmed Soomro, Suhail; Unar, Imran Nazir; Akhter, Faheem (Penerbit Universiti Kebangsaan Malaysia, 2022)
Globally, large reserves of low grade or lignite coal are available. Low-ranking coal contains high mineral content, moisture content, and low calorific value. The major problem in coal is sulphur and ash When used for combustion, this type of coal imposes harmful impacts on the environment. It results in the production of greenhouse gases and ash, which are hazardous for the environment and human health. Usually, the demineralization and desulphurization process is used to remove the minerals matters before its use in industrial processes such as combustion, carbonization, gasification and liquefication. Which are harmful to the environment if combusted untreated. Therefore, the number of upgrading technology is being used to reduce the mineral matters from coal and save the environment. The current paper reviews the potential of demineralization and desulphurization processes to enhance the usability of lignite coal. Moreover, it focuses on preserving the high-grade coal which is already depleted in abundance.